Payroll taxes, social insurance and business cycles - Michael C. Burda; Mark Weder (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
Payroll taxes represent a major distortionary in uence of governments on labor markets. This paper examines the role of payroll taxation and the social safety net for cyclical fluctuations in a nonmonetary economy with labor market frictions and unemployment insurance, when the latter is only imperfectly related to search effort. A balanced social insurance budget renders gross wages more rigid over the cycle and, as a result, strengthens the model's endogenous propagation mechanism. For conventional calibrations, the model generates a negatively sloped Beveridge curve as well as substantial volatility and persistence of vacancies and unemployment.
Keywords: E24; J64; E32; 330; business cycles; labor markets; payroll taxes; unemployment; consumptiontightness puzzle; Lohnsummensteuer; Steuerwirkung; Arbeitslosenversicherung; Konjunkturelle Arbeitslosigkeit; Arbeitsplatzsuchmodell; OECD-Staaten